El mecanismo tributario del saldo a favor del exportador y su incidencia en la rentabilidad de las empresas agroindustriales, región La libertad, año 2015. - Gomez Chicoma, Indira Estefany (2016)
This research deals with the tax mechanism balance in favor of the exporter and the impact of its application on the profitability of the company. The study begins with the analysis of the tax mechanism based on information recorded as purchases and sales exported by determining the amount of the credit balance to be requesting, we proceed to compare the use of this return in the financial statements and changes in the items in the Statement of Financial Position and Results and otherwise change the games as not to apply such Balance to Favor; and therefore the profitability and the benefits obtained by the successful and utility ratios used before and after the use of the credit balance of the Exporter is evaluated. The method used is the inductive - descriptive and the population of this research consists of the economic and financial information companies Agroindustrial La Libertad, for shows of this was taken as a reference to the Agroindustrial SAC Avocado Packing Company. Finally, the analysis and comparison of applying the credit balance with the financial ratios obtained shows greater liquidity to cover short-term obligations, the debt ratio decreased along with financial costs and return on sales, equity and fixed assets sane was favorable to net income obtained in the income Statement.